POLITICAL AND LEGAL DEVELOPMENT OF SUSTAINABLE TOURISM VILLAGES: (Study on Flower Villages in Tawangrejeni Village, Turen, Malang Regency) - Joice Soraya; Galih Setya Refangga (Transpublika Publisher, 2024)
This study examines the legal politics and initiatives aimed at establishing sustainable tourism villages in Kampung Kembang, Tawangrejeni Tourism Village, Turen District, and Malang Regency. The legal politics focus on developing legislation that promotes sustainable tourism, fosters sustainable management, and ensures social, economic, cultural, and environmental sustainability. The development strategies include improving attractions, accessibility, amenities, community empowerment and entrepreneurship, human resource capacity, stakeholder collaboration, digital technologies, waste management, and financial resources. The establishment of sustainable tourism villages is intended to help achieve the Sustainable Development Goals (SDGs) in economic, ecological, social, and cultural areas. Development activities must be holistic and integrated, engaging multiple sectors. With the appropriate legal politics and comprehensive development initiatives, Kampung Kembang is intended to become a model for a sustainable tourism village that benefits the community while protecting nature and culture.